2021
DOI: 10.1186/s12950-021-00269-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of melatonin in the angiogenesis potential; highlights on the cardiovascular disease

Abstract: Melatonin possesses multi-organ and pleiotropic effects with potency to control angiogenesis at both molecular and cellular levels. To date, many efforts have been made to control and regulate the dynamic of angiogenesis modulators in a different milieu. The term angiogenesis or neovascularization refers to the development of de novo vascular buds from the pre-existing blood vessels. This phenomenon is tightly dependent on the balance between the pro- and anti-angiogenesis factors which alters the functional b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 86 publications
0
8
0
1
Order By: Relevance
“…It has been indicated that the exposure of hypoxic cells to melatonin can reduce the production of angiogenesis factors [ 39 ]. Melatonin can diminish the expression of HIF-1α via the neutralization of reactive oxygen species and regulation of Sphingosine kinase 1 activity and TGF-β signaling pathway [ 40 , 39 , 41 ]. The reduction of reactive oxygen species and down-regulation of VEGF were documented in hypoxic ECs treated with melatonin [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that the exposure of hypoxic cells to melatonin can reduce the production of angiogenesis factors [ 39 ]. Melatonin can diminish the expression of HIF-1α via the neutralization of reactive oxygen species and regulation of Sphingosine kinase 1 activity and TGF-β signaling pathway [ 40 , 39 , 41 ]. The reduction of reactive oxygen species and down-regulation of VEGF were documented in hypoxic ECs treated with melatonin [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of Mel was done with the respect to the fact that this hormone can blunt the detrimental effects of reactive free radicals in the early days after transplantation before the formation of de novo vessels [ 33 , 34 ]. Besides, this hormone can increase the local content of pro-angiogenesis factors from ECs and immune cell origin [ 35 ]. According to our data, Mel- and ECs-free Alg + Fib hydrogels lack eligibility to induce angiogenesis as compared to the FT group.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the AP, Wnt Inhibitory Factor-1 knockout mice displayed an elevated level of the GLUT1 BBB marker [ 29 ], suggesting that locally expressed endogenous inhibitors of Wnt/β-catenin signaling suppress vEC’s β-catenin activities to prevent BBB formation in the fenestrated vascular beds of the brain. Melatonin, a hormone secreted by the PG, has been implied in the regulation of angiogenesis [ 205 ], especially inhibition of multiple tumor angiogenesis; however, its role in fenestrated capillary development or maintenance in the PG remains unclear.…”
Section: Development and Maintenance Of Endothelial Fenestrations And...mentioning
confidence: 99%